2011
DOI: 10.1074/jbc.m111.292474
|View full text |Cite
|
Sign up to set email alerts
|

Small-angle X-ray Scattering Studies of the Oligomeric State and Quaternary Structure of the Trifunctional Proline Utilization A (PutA) Flavoprotein from Escherichia coli

Abstract: Background:Trifunctional proline utilization A (PutA) proteins are multifunctional flavoproteins that catalyze two reactions and repress transcription of the put regulon. Results: PutA from Escherichia coli is a V-shaped dimer, with the DNA-binding domain mediating dimerization. Conclusion: Oligomeric state and quaternary structures are not conserved by PutAs. Significance: The first three-dimensional structural information for any trifunctional PutA is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 51 publications
2
37
0
Order By: Relevance
“…The poor prediction of the oligomeric state for Escherichia coli proline utilization A is likely to be owing to the unusual shape of this protein. SAXS shape reconstructions show that the dimeric particle is highly elongated, with dimensions of 205 Â 85 Â 55 Å (Singh et al, 2011). As shown next, highly elongated proteins deviate substantially from power-law behavior.…”
Section: Predicting Oligomeric State From An Experimental Measurementmentioning
confidence: 87%
“…The poor prediction of the oligomeric state for Escherichia coli proline utilization A is likely to be owing to the unusual shape of this protein. SAXS shape reconstructions show that the dimeric particle is highly elongated, with dimensions of 205 Â 85 Â 55 Å (Singh et al, 2011). As shown next, highly elongated proteins deviate substantially from power-law behavior.…”
Section: Predicting Oligomeric State From An Experimental Measurementmentioning
confidence: 87%
“…Experiments that are described as anaerobic were subjected to vacuum/nitrogen gas cycles followed by the addition of protocatechuate dioxygenase (0.05 unit/ml) and protocatechuic acid (100 M) to scrub the remaining oxygen as described previously (17). (20), which is based on small angle x-ray scattering, crystal structures of EcPutA DNA-binding and PRODH domains, and homology to BjPutA. The DNA-binding, PRODH, and P5CDH domains are colored as in the domain diagram.…”
Section: Experimental Prodceduresmentioning
confidence: 99%
“…Tyr-58 is proposed to move and thereby allow ammonia to enter the 40 Å channeling pathway to the NAD ϩ synthetase active site (48). Molecular dynamics simulations of PutA could provide key insights to help explain our kinetic observations and further test a channel gating hypothesis (12,20). Other conformational changes not yet known may also contribute to the activation of EcPutA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SAXS showed that EcPutA forms an elongated V-shaped dimer with radius of gyration ( R g ) of 63 Å and dimensions of 205 × 85 × 55 Å [42]. Domain deletion analysis and SAXS rigid body modeling show the RHH domain mediates dimerization at the centroid of the particle, and the catalytic modules (residues 85–1320) reside in the large outer lobes.…”
Section: Three-dimensional Structure Of Putamentioning
confidence: 99%